2016
DOI: 10.1136/bmjopen-2015-010639
|View full text |Cite
|
Sign up to set email alerts
|

General practitioners’ justifications for therapeutic inertia in cardiovascular prevention: an empirically grounded typology

Abstract: ObjectiveTo construct a typology of general practitioners’ (GPs) responses regarding their justification of therapeutic inertia in cardiovascular primary prevention for high-risk patients with hypertension.DesignEmpirically grounded construction of typology. Types were defined by attributes derived from the qualitative analysis of GPs’ reported reasons for inaction.Participants256 GPs randomised in the intervention group of a cluster randomised controlled trial.SettingGPs members of 23 French Regional Colleges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The protocol in this research, intentionally designed to minimise bias, is apparently not compatible with routine daily practice in primary care. 17,50 This is reflected in the discrepancy between the a priori calculated sample size and the number of included patients in this research. Although the planned number of screened patients was not reached, nonetheless a prevalence estimate was achieved with a narrow confidence margin (95%, CI = 1.4 to 4.9).…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
“…The protocol in this research, intentionally designed to minimise bias, is apparently not compatible with routine daily practice in primary care. 17,50 This is reflected in the discrepancy between the a priori calculated sample size and the number of included patients in this research. Although the planned number of screened patients was not reached, nonetheless a prevalence estimate was achieved with a narrow confidence margin (95%, CI = 1.4 to 4.9).…”
Section: Comparison With Existing Literaturementioning
confidence: 94%
“…Conversely, there was a significant improvement in recommended prescribing of appropriate treatments among those at high CVD risk in the post‐trial period both for the intervention and control groups. The delayed onset of improvement in the intervention group might be related to doctors not prescribing recommended medications immediately following institution of lifestyle change recommendations or initiatives, or a generally more cautious approach to introducing or accepting new treatments . The improvement in prescriptions in the control group during the post‐trial period suggests the intervention had an impact outside the trial setting, although there are obvious limitations in making this assertion given the observational and uncontrolled nature of the study design.…”
Section: Discussionmentioning
confidence: 99%
“…The delayed onset of improvement in the intervention group might be related to doctors not prescribing recommended medications immediately following institution of lifestyle change recommendations or initiatives, or a generally more cautious approach to introducing or accepting new treatments. 22 The improvement in prescriptions in the control group during the post-trial period suggests the intervention had an impact outside the trial setting, although there are obvious limitations in making this assertion given the observational and uncontrolled nature of the study design. The secular effects of wider distribution of a new guideline advocating for an absolute risk approach to management of cardiovascular risk may have also had relevance to the observed change.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from many different settings and countries have demonstrated the existence of clinical inertia. Reasons for clinicians' not intensifying therapy have been studied, and a detailed typology for these reasons has been developed . Reasons for clinical inertia include unwarranted optimism, overconcern about adverse effects, and willingness to further negotiate care.…”
mentioning
confidence: 99%
“…Reasons for clinicians' not intensifying therapy have been studied, and a detailed typology for these reasons has been developed. 9 Reasons for clinical inertia include unwarranted optimism, overconcern about adverse effects, and willingness to further negotiate care. It has been suggested that clinicians may not be intensifying therapy due to uncertainty as to what is the patient's "true" blood pressure.…”
mentioning
confidence: 99%